OPTIMALISASI KOMPETENSI GURU DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH RAUDHATUL JANNAH: Penelitian Kualitatif - Nursifa Hasanah; Idarianty; Abdullah Yunus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to optimize teacher competence in improving the quality of education at Madrasah Tsanawiyah Raudhatul Jannah, located in Semua Village, Bram Itam District, Tanjung Jabung Barat Regency. The main issues identified in this institution include teachers teaching subjects outside their educational background, the low number of teachers holding teaching certificates, and the presence of teachers who do not meet the qualification standards mandated by law, such as high school graduates teaching Mathematics. This research employed a qualitative approach using the snowball sampling method. The research subjects consisted of the principal as the key informant, three teachers (Mathematics, English, and Al-Qur’an Hadith), students, and parents.The findings reveal that the teachers’ competence was initially suboptimal and did not meet educational quality standards. To address this, three strategies were implemented: (1) professional training and development programs facilitated by the Ministry of Religious Affairs, (2) socialization and enforcement of school regulations, and (3) provision of financial incentives through the Village Medium-Term Development Plan (RPJMDes) in the form of direct cash assistance for teachers. Following the implementation of these strategies, teacher competence at Madrasah Tsanawiyah Raudhatul Jannah significantly improved and met the established standards of educational quality.